The potential of alliances for regional productive development from the Tutorial Centers of the University of Cartagena measured with the support of Plithogenic SWOT Analysis - Edgardo Antonio Carmona-Arrieta; Katia Ninozca Flores-Ledesma; Álvaro Andrés Escobar-Espinoza; Abrahan Cesar Neri-Ayala; Pedro Barrientos-Gutiérrez; Pablo José Guerrero (Neutrosophic Sets and Systems)
The University of Cartagena in Colombia, with its 104 recognized research groups in various fields such as health, social sciences, engineering, basic sciences, environment, and sustainable development, expands its academic reach by establishing Tutorial Centers in Bolívar and Córdoba. The objective of these centers is to offer distance learning opportunities, thus increasing access to education for the local population. This study explores the potential of forming strategic alliances with the productive sector, taking advantage of the resources and strategic benefits of these centers. In this paper, we measure the potentialities, based on the Plithogenic SWOT Analysis. The SWOT analysis is used to measure the possible strengths, weaknesses, opportunities, and threats to the development of an organization or a project. In particular, the potentialities are calculated as the combination of strengths and opportunities. On the other hand, the variables to be measured are multiple and of different natures, which is why we use the Plithogeny theory. For the study, we used the opinion of a group of 5 experts.